PERAN KOMUNIKASI KOMUNITAS BANGKIT PENGUSAHA MUSLIM (BPM) DALAM MENSOSIALISASIKAN PRODUK HALAL KEPADA PELAKU UMKM BIDANG KULINER DI KOTA PEKANBARU - M. Afri Yanda; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Bangkit Pengusaha Muslim Community Sharia-based are present to assist the government in communicating halal products to UMKM in the city of Pekanbaru. The purpose of this community is to help the people, especially those in Pekanbaru, so that their business is in accordance with Islamic law. The purpose of this study was to determine the role of communication of Bangkit Pengusaha Muslim Community in socializing halal products to UMKM (culinary) in the city of Pekanbaru as seen from the role of communication and obstacles while socializing halal products.In this research, the method used is descriptive qualitative. The subjects of this study amounted to four people, consisting of the Founder of  Bangkit Pengusaha Muslim (BPM), a Member of BPM, two UMKM Partners of Muslim culinary products in the Pekanbaru city. While the object of this research is the role of communication of the Bangkit Pengusaha Muslim Community in disseminating halal products to micro and small businesses in the Pekanbaru city. Data collection techniques used were observation, interviews and documentation. Data analysis techniques using an interactive data analysis model. In achieving data validity in this study, the authors used an extension of participation and triangulation.The results showed that the communication role of the Bangkit Pengusaha Muslim Community (BPM) had two roles in socializing halal products to UMKM, namely as an information center where the Bangkit Pengusaha Muslim Community (BPM) became a gathering place for Muslim entrepreneurs to unite and develop together by providing useful information for the development of businesses owned by Muslim entrepreneurs. One of the information shared by the BPM community is information about halal products. And as a companion where providing input and direction to the UMKM. Inputs and direction given by the BPM community aims to ensure that UMKM always maintain the production of halal and toyiban marketing in accordance with Islamic law. Meanwhile the obstacles that occur in socializing halal products in the form of media barriers and material obstacles in production.Keywords : role of comunication, Community, halal product.